Terra sigillata z cmentarzyska kultury przeworskiej w Konopnicy, województwo sieradzkie - Tyszler, Lubomira (Acta Universitatis Lodziensis. Folia Archaeologica, 1997)
The excavations at the cemetery in Konopnica resulted in finding 114 fragments of terra sigillata from graves (Tab. 1) and 52 that were found loose. About 40% оf the whole collection was attributed to a certain producer or at least a workshop (Tab. 2, 3). The set is badly preserved, partially destroyed in fire of funeral pyres. The analysis revealed that the fragments of vessels come from the Rhineland workshops in Rheinzabern and the Rhaetia ones in Westerndorf and Pfaffenhoffen. Forms of vessels are represented by bowls Drag. 37. The analysis of terra sigillata fragments found in the graves proves that they were treated in the same way of breaking and burning in piles as hand-made vessels or turnery ones. They were also divided among the dead, e.g. fragments of Comitialis bowel from Westerndorf were found in four different graves (Tab. 4). Terra sigillata is known from the graves of various category, from the rich ones, as well as, from the poor (Tab. 5-7). Terra sigillata might have been a sort of the „souvenir of Imperium” for people from Barbaricum although it is unknown whether their owners had enough awamess of their provenance. The cemetery in Konopnica dates back from the Late La Tene period A2-A3 to the phase D of the Migration of Nations period. Terra sigillata collected there dates back from the half of the phase B2/C1 to the end of the phase Cl. The forms are clearly connected with the flow of import after the Markomanian wars.